Cavity ring down spectroscopy: a method to measure sputter erosion for EP applications - Surla, Vijay K., author; Yalin, Azer, advisor; Williams, John, committee member; Wilbur, Paul, committee member; Collins, George, committee member (Colorado State University. Libraries, 2007)
Sputter erosion is a critical process in many electric propulsion (EP) devices from the point of view of both lifetime and contamination assessment. The present research develops cavity ring-down spectroscopy (CRDS) as a diagnostic tool to quantify sputter erosion. Measurements of sputtered particle number density and velocity are presented for a variety of target materials. The number density measurements are validated by comparison with a simple sputter model. The CRDS velocity measurements are obtained by a Doppler shift method and are validated by comparison with sputter simulations and Laser Induced Fluorescence (LIF) measurements. A method to obtain differential sputter yield measurements (angular information) is developed and presented. The approach is to scan the optical-axis relative to the source of sputtered particles and to use modeling to relate the resulting spatial profile to the differential sputter yield profile from the spatial profile. Demonstrative measurements are presented and validated by comparison with Quartz Crystal Microbalance (QCM) measurements. Species-specific measurements of sputtering from multi-components material presented and show that the sputtering characteristics change relative to sputtering of pure samples. Finally, experiments investigating the excited state distributions of sputtered particle, and state-specific velocity distributions, are reported.
Keywords: mechanical engineering